Biodanza and Other Dance Forms as a Vehicle for Social-Emotional-Learning in Schools: A Scoping Review (LEARNing Landscapes, 2022)
In this scoping review, the literature on the relationship between dance and Social Emotional Learning (SEL) was consolidated. Research of various forms of dance on psychosocial outcomes among K-6 populations included: increased sense of belonging, violence prevention, and increased creative thinking and problem-solving responses. The dance form, Biodanza, in particular, may be useful in engaging students in the active practice of social skills, appropriate use of body language, self-regulation, self-awareness, and boundaries. We suggest that using dance as a tool for SEL in the classrooms may contribute to improved student mental health and to more inclusive schools.
Keywords: SEL; Social-Emotional-Learning; dance; schools; children